A critical assessment of Guyana's sustainability pathway: Perspectives from a developing extractive economy. (June 2022) - Mentis, Alan; Moonsammy, Stephan
Abstract: The primary purpose of this research article is to present existing and forecasted sustainability indicators for Guyana in order to assess the country's sustainable development pathway. Genuine Savings, Carbon Emissions and Forest Cover were selected as appropriate measures of weak sustainability to investigate the country's sustainability trajectory. Further exploration of macro-economic variables such as natural capital stocks, wealth accumulation, resource rents and economic growth as empirical indicators, revealed that despite the effective forest management policies currently implemented in the country, Guyana is not on a sustainable pathway especially on the outlook for Genuine Savings. The country will experience an increase in economic growth primarily from the expansion of its oil sector. The potential boom in the economy from the non-renewable oil industry will provide a surge in foreign exchange that will require a robust investment structure to utilize resource rents in building the country's renewable capital stock. Positive Carbon Emission predictive trends emerging from this study are indicative of the country's growth towards more carbon intensive industries as the potential oil industry can stimulate a positive emission rating globally, indirectly from downstream industries on the international markets that purchases the country's oil. Highlights: Empirical evidence shows that Guyana is not on a sustainable pathway. Forecasts demonstrates unsustainable economic growth by 2030. The projection for Forest Cover demonstrates a further decrease in deforestation by 2030. Policy environment has a national dependence on its extractive industry.